Bioclimatic modeling of the distribution of brown marmorated stink bug Halyomorpha halys (Stål, 1855), with special reference to Ukraine - Tytar, V.M.; Kozynenko, I.I. (Доповіді НАН України, 2020)
Due to the potential severity of the impact of brown marmorated stink bug Halyomorpha halys both in terms of the plant susceptibility and economic loss and the border detection of the bug in the seaport city of Odesa, it is important to determine the potential suitable bioclimatic range in Ukraine. The bioclimatic modeling suggests that, under the current climate conditions, the pest has varying chances in the near term to invade a number of regions in Ukraine, especially in the south of the country: Transcarpathia, Crimea, portions of Odesa, Mykola¿v, Kherson, and Zaporizhzhya regions.